THE IMPLICATIONS OF THE SPECIALIZATION OF ASEPSIS AND ANTISEPSIS METHODS IN MEDICAL ASSISTANCE IN DIFFERENT SYSTEMIC PATHOLOGIES - Kamel Earar; Oleg Solomon; Doriana Agop Forna; Tiutiucă Carmen; Focșăneanu Sergiu Ciprian; Marian Ilie; Anca Petronela Moșneagu; Denisa Marin Batir; Emil Ceban (Romanian Society of Oral Rehabilitation, 2023)
Sterilization and disinfection are the basic components of hospital infection control activities. Every day, hospitals perform various surgical procedures. More invasive procedures are also performed in various health care facilities. The medical device or surgical instrument that comes into contact with sterile tissue or the patient's mucosa during various procedures is associated with an increased risk of introducing pathogens into the patient's body. Healthcare providers are equally responsible for reducing and eliminating such infections. Each hospital should have its own sterilization and disinfection guidelines based on the intended use of medical devices and possible associated infections. Currently, there is an increase in the frequency of newly emerging and multidrug-resistant pathogens in all health care settings. Therefore, medical personnel, laboratory people and health care providers should have better knowledge about these techniques to prevent the spread of these pathogens